Nurses’ Roles in Caring Children with Febrile Convulsion - Pidjadee, Chakkrich; Maytapattana, Muntanavadee; Prasitsart, Natthanya (Journal of The Royal Thai Army Nurses, 2021)
Febrile convulsion is a common disease found in children at the age of 6 months – 5 years. Although the prognosis is rather effective, it makes caregivers feel much worried, and there will be several impacts in the case that children have recurrent seizures. Nurses have significant roles in utilizing the nursing process to do screening of children upon admission, involving in finding causes of fever, providing care for children during seizures, handling fever and preventing recurrent seizures, as well as preparing caregivers for fever handling at home and initial assistance for children in case of having febrile convulsion. Therefore, this article aims to present the data regarding febrile convulsion and role of nurses in providing care for children with febrile convulsion so that nurses acquire guidelines on planning and providing care for children with febrile convulsion efficiently, and that will further contribute to good quality of life of children and caregivers.